C-Reactive Protein and Interleukin-6 Correlated with Resistin Level in Liver Cirrhosis - I Ketut Mariadi; Hendra Koncoro; I Dewa Nyoman Wibawa (The Indonesian Society for Digestive Endoscopy, 2020)
Background: The incidence of insulin resistance is very high in liver cirrhosis. Resistin is thought to be one of the factors contributing to the occurrence of insulin resistance. Liver Cirrhosis is a chronic inflammatory condition. C-reactive protein (CRP) and interleukin-6 (IL-6) are inflammatory mediators, which are associated with the severity of liver damage. Resistin also increases in liver cirrhosis. This study aimed to determine whether CRP and IL-6 levels were correlated with resistin levels in patients with liver cirrhosis.Method: An analytic cross-sectional study was conducted, in cirrhosis patients, to determine CRP and IL-6 levels as markers of the inflammatory process and blood resistin levels.Results: In this study was found, CRP and IL-6 levels were associated with the severity of liver cirrhosis. Resistin levels are associated with the severity of cirrhosis of the liver. CRP and IL-6 levels are positively correlated with resistin levels and as independent predictors of resistin levels.Conclusion: This study concluded that CRP and IL-26 levels are correlated with resistin levels and as independent predictors of resistin levels in liver cirrhosis patients.